2004
DOI: 10.1093/ndt/gfh137
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced tubulo-interstitial nephritis secondary to proton pump inhibitors: experience from a single UK renal unit

Abstract: Drugs are the most common cause of interstitial nephritis in the population studied. Those drugs most commonly associated with interstitial nephritis were the proton pump inhibitors omeprazole and lansoprazole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 17 publications
2
64
0
3
Order By: Relevance
“…Despite a dearth of clinical studies in critically ill patients [8], many ICUs are now using PPI to prevent stress-related GI bleeding. The onset of action of PPIs has been shown to be quite rapid.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite a dearth of clinical studies in critically ill patients [8], many ICUs are now using PPI to prevent stress-related GI bleeding. The onset of action of PPIs has been shown to be quite rapid.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was shown that gastric acid suppression therapy was also associated with an increased risk of community-acquired pneumonia [7]. Moreover, PPIs are an important cause of drugassociated tubulointerstitial nephritis [8] and have been linked to increased risk of enteric infections including Clostridium difficile-associated diarrhea [9]. Therefore, the use of PPIs should be carefully considered for each patient.…”
Section: Introductionmentioning
confidence: 99%
“…Studies suggest that AIN is the cause of 6%-8% of episodes of acute renal failure (ARF). 11,12 The diagnosis of AIN seems to be most prevalent in renal biopsies in which there is unexplained renal impairment in the presence of an inactive urinary sediment, ie, lack of heavy proteinuria, significant hematuria, or presence of dysmorphic red blood cells. In this setting AIN has been reported to occur in as many as 25% of cases.…”
mentioning
confidence: 99%
“…The duration of proton pump inhibitor treatment before presentation is usually between two weeks and nine months. 4 The temporal relationship in this case suggests that omeprazole was the most likely cause of interstitial nephritis, although the possibility that amoxycillin, pantoprazole or the NSAID were implicated cannot be excluded.…”
Section: Commentmentioning
confidence: 78%